2014
DOI: 10.3810/pgm.2014.10.2817
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Lorcaserin: A Combined Analysis of the BLOOM and BLOSSOM Trials

Abstract: This pooled analysis of the phase III BLOOM and BLOSSOM trials shows that lorcaserin 10 mg twice daily, in combination with diet and exercise, is safe and tolerable, and is associated with statistically significant weight loss and clinically relevant improvements in cardiometabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 36 publications
1
69
1
Order By: Relevance
“…Lorcaserin elicits average weight loss of about 3.2 kg more than placebo (better than orlistat but still poor) and there are worries about its preclinical safety and psychiatric risks. There is no evidence that it increases valvulopathy [15], which was the main cause of the demise of the 5HT releasers and reuptake inhibitors fenfluramine and dexfenfluramine. This may remain a concern in the minds of some regulators, however.…”
Section: Disappointments Past and Presentmentioning
confidence: 99%
“…Lorcaserin elicits average weight loss of about 3.2 kg more than placebo (better than orlistat but still poor) and there are worries about its preclinical safety and psychiatric risks. There is no evidence that it increases valvulopathy [15], which was the main cause of the demise of the 5HT releasers and reuptake inhibitors fenfluramine and dexfenfluramine. This may remain a concern in the minds of some regulators, however.…”
Section: Disappointments Past and Presentmentioning
confidence: 99%
“…Overall effect size was modest (Kennett and Clifton 2010;Heal et al 2012, Bray andRyan 2014), with a 3.2 kg weight loss compared to placebo, approximating to a 3 % weight change. A meta-analysis of the BLOOM and BLOSSOM trials has been recently reported (Aronne et al 2014) and includes data from 6388 patients. By week 52, more than twice as many lorcaserin (10 mg b.i.d.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, lorcaserin is well tolerated and decreases food intake and body weight (Smith et al, 2009(Smith et al, , 2010Chan et al, 2013;Aronne et al, 2014) at doses that have low potential for producing heart valve disease (Weissman et al, 2013) or abuse (Shram et al, 2011), effects commonly associated with 5-HT 2B and 5-HT 2A receptor agonists, respectively (Nichols, 2004;Hutcheson et al, 2011). In addition to preclinical studies demonstrating that lorcaserin decreases food intake and body weight (Smith et al, 2008;Thomsen et al, 2008;Higgins et al, 2013b;Grottick et al, 2015), lorcaserin is also shown to decrease nicotine selfadministration and the reinstatement of responding for nicotine in rats (Levin et al, 2011;Higgins et al, 2012Higgins et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%